Hak Anti Diskriminasi Dan Upaya Hukum Bagi Tenaga Kerja Lanjut Usia Dalam Sektor Pekerjaan - Amalia Tiara Kasih Subrianto; Rani Apriani (Universitas Widya Gama Malang, 2022)
The necessity of working to meet daily needs is not only for people who are at a young age or productive age. This unreasonable reason is already outside of the provisions according to Law Number 13 of 1998 concerning Elderly Welfare and Law Number 13 of 2013 concerning employment. Where the elderly are given rights, one of which is the service of job opportunities. In addition to the workplace, there is also age discrimination among job applicants. This is because there is an age limit for the job you want to apply for, even if they actually meet the right qualifications. The research method used is normative legal research that seeks to produce a systematic explanation of the legal norms governing certain categories of laws. Based on the results obtained, although these elderly workers have been protected by law, their implementation is not appropriate. The causes that hinder this can come from two factors, namely prejudices and stereotypes that result in elderly workers experiencing discrimination such as demotion or demotion which can end in termination of employment